PENGARUH KEPEMILIKAN PEMERINTAH, UKURAN KAP, DAN BOARD AGE TERHADAP PENGUNGKAPAN PENGENDALIAN - Totok Dewayanto (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2020)
This study aims to examine the effect of government ownership, KAP size, and board age on disclosure of internal control. Company size is used as a control variable in this study. The object of this research is manufacturing companies listed on the Indonesia Stock Exchange in 2016 - 2017. This study used a sample of 226 companies using the purposive sampling method. The statistical technique used in this study is multiple linear regression. The results showed that government ownership had a positive and significant effect on disclosure of internal control, while board age had a negative and significant effect on disclosure on internal control. This study did not find any significant effect from KAP size on disclosure of internal control